[PP.25.39] NUTRACEUTICAL EFFECTS ON GLUCOSE AND LIPID METABOLISM IN PATIENTS WITH IMPAIRED FASTING GLUCOSE: A PILOT, DOUBLE-BLIND, PLACEBO-CONTROLLED, RANDOMIZED CLINICAL. (September 2017) - Cicero, A.F.G.; Morbini, M.; Colletti, A.; Fogacci, F.; Bove, M.; Veronesi, M.; Giovannini, M.; Borghi, C.
Abstract : Objective: A number of natural compounds has individually demonstrated to improve the glucose and lipid levels in humans. The aim of this pilot study was to evaluate the short-term glucose and lipid-lowering activity in subjects with impaired fasting glucose. Design and method: To assess the effects of a combination of nutraceuticals based on Lagerstroemia speciosa, Berberis aristata, Curcuma longa, Alpha-lipoic acid, Chrome picolinate and Folic acid we performed a double bind, placebo-controlled, randomized clinical trial in 40 adults affected by impaired fasting glucose (FPG = 100–125 mg/dL) in primary prevention of cardiovascular disease. After a period of 2 weeks of dietary habits correction only, patients continued the diet and began a period of 8 weeks of treatment with nutraceutical or placebo. Data related to lipid pattern, insulin resistance, liver function and hsCRP have been obtained at the baseline and the end of the study Results: No side effects have been detected in both groups of subjects. After the nutraceutical treatment, and compared to the placebo treated group, the enrolled patients experienced a significant improvement in TG (−34, 7%), HDL-C (+13.7), FPI (−13.4%), and HOMA-Index (−25%) versus the baseline values. No changes have been observed in the other investigated parameters in both groups (Body Mass Index, LDL-C, hsCRP). Conclusions: The tested combination of nutraceuticals has shown clinical efficacy in the improvement of TG, HDL-C, FPI and HOMA-Index, with an optimal tolerability profile. Further confirmation are needed to verify these observations on the middle and long term with a larger number of subjects.